Can price regulation based on income groups help to solve the environmental-nutritional dilemma of the Chinese diet? - Rui Li; Meng Li; Yang Yang; Yanan Wang; Wei Chen; Peixue Xing; Zengming Liu (Sustainable Futures)
Dietary adjustment is widely recognized as an effective way to solve the environment or health predicament, but price regulation's efficacy in balancing nutrition and sustainability remains unclear. This study evaluated the changes in environmental impacts and nutritional benefits of dietary patterns resulting from price regulation across income groups in China from 2000 to 2022. The results revealed that food expenditures in urban areas were significantly higher than in rural areas. And rural areas exhibiting a more pronounced increase in food expenditures as income rose. Nutritional intake disparities among income groups were substantially greater in rural areas. And the rural middle-income group demonstrated the highest intake of calories and nutrients such as fiber, saturated fat and vitamin A. This study assessed the environmental hazards of diets using indicators including greenhouse gas emissions, freshwater use and land use. Higher-income groups exhibit greater impacts on diet-related greenhouse (GHG) emissions, nitrogen application, eutrophication emissions and acidification emissions. The highest-income group displayed heightened responsiveness to fruits and beef. Imposing differentiated consumption taxes on higher income groups and providing price subsidies to lower income groups are effective in reducing greenhouse gas emissions and improving nutrition.